Tuning interfacial energy barriers in heterojunctions for antiinterference sensing - Zhao,M; Yu,J; Zhang,X; Li,Z; Ding,Y; Edel,JB; Ma,Y; Li,H (Advanced Functional Materials, 2021)
Analytes with similar redox properties are normally difficult to distinguish through classic electrochemical methods. This becomes especially true for the onsite detection in seawater where the high salinity and complex chemical components can impose severe interference. Hereby introducing numerous nanoscale heterojunctions in the Cu/CuO/reduced graphene oxide (rGO)/polypyrrole (PPy) and Cu/CuO/rGO/chitosan electrochemical sensors, tunable interfacial energy barriers to exponentially regulate the electrochemical signal can be constructed. Importantly, these energy barriers are independent to redox but closely related to the electrostatic interaction from absorbed charged analytes such as Hg2+ and Cu2+. Moreover, the similar sensing principle is also valid for the energy barriers in pn junctions as demonstrated in the Ni/NiO/ZnO/PPy sensor. The good antiinterference properties and ultrahigh sensitivity of this sensing mode offers new opportunities in trace analyte detection in harsh environments such as seawater.